The role of green finance in reducing CO2 emissions: An empirical analysis - Muhammad Saeed Meo; Mohd Zaini Abd Karim (Borsa İstanbul Review, 2022)
This study examines the relationship between green finance and carbon dioxide (CO2) emissions in the top ten economies that support green finance (Canada, Denmark, Hong Kong, Japan, New Zealand, Norway, Sweden, Switzerland, the United Kingdom, and the United States). This study uses quantile on quantile regression (QQR), introduced by Sim and Zhou (2015), to examine the dependence structure between different quantiles of green finance and CO2 emissions. Our overall findings confirm the negative impact of green finance on CO2 emissions; however, this relationship varies across the different quantiles of the two variables. This variation might be due to green finance market conditions (e.g., bearish or bullish) and country-specific market conditions. The findings in the study confirm that green finance is the best financial strategy for reducing CO2 emissions.
Keywords: 330; CO2 emissions; Green bonds; Green finance; Quantile on quantile regression